Isolation, identification of antimicrobial activity-possessing marine actinomycetes and fungi from samples collected at the Bach Long Vy to Ly Son islands - Quyen, Vu Thi; Hong Minh, Le Thi; Mai Anh, Nguyen; Cuong, Pham Van; Thu Huyen, Vu Thi; Mai Huong, Doan Thi (Vietnam Journal of Biotechnology, 2023)
The marine environment has been known as a resource containing a lot of compounds with antibiotic, anti-tuberculosis and antiviral activities. Many of the marine microorganisms have been found to live in sediment, sand, surface or within the body of other living organisms such as sponges, soft coral, mollusk, algae… Natural products from marine actinomyces and fungi are considered an important source for the discovery of novel compounds, of their rich secondary metabolites. From 38 samples collected at 22 coordinates and different depths in the sea from Bach Long Vy island - Hai Phong to Ly Son island - Quang Ngai on the marine research vessel “Oparin Academik”, 40 actinomycetes and 20 fungal strains were isolated. The crude extracts of 60 isolates were primary screened for their antimicrobial activity against 7 pathogenic microorganisms by the Bioassay method in a 96-well tray. As a result, 53/60 strains were resistant at least 1 tested microorganisms, 22/60 isolates against 3 or more the test microorganisms, respectively. In particular, there were 4 isolates (three actinomyces G817, G819, G824 and fungus OM01) with the strongest resistance to four or more tested strains, which were then studied further. The results of phenotypic and molecular identification by 16S rRNA sequences for G817, G819, G824 and 18S rRNA sequence for OM01 showed that OM01 was Penicillium citrinum; G817, G819 strains belonged to Salinispora arenicola, while G824 was identified as Pseudonocardia carboxydivorans. The promising candidate isolates were analyzed in a phylogenetic tree based on MegaX software.